2021
DOI: 10.34117/bjdv7n10-027
|View full text |Cite
|
Sign up to set email alerts
|

Complicações decorrentes do uso do cateter central de inserção periférica (PICC) em uma unidade de terapia intensiva neonatal / Complications arising from the use of peripherally inserted central catheter (PICC) in a neonatal intensive care unit

Abstract: Introdução: A terapêutica intravenosa tem é fundamental na assistência desses neonatos que frequentemente necessitam de medicamentos de uso prolongado. Objetivo: Caracterizar os recém-nascidos (RN) que fizeram uso do Cateter Venoso Central de Inserção Periférica (PICC) e identificar as complicações advindas do uso deste dispositivo. Método: Estudo descritivo e quantitativo que foi desenvolvido em um hospital público de Belo Horizonte, Minas Gerais. A coleta de dados foi realizada por meio do preenchimento de u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
5
0
6
Order By: Relevance
“…5 In a study on the birth weight of NBs performed in Minas Gerais, 49% of these had a weight below 2500 grams, another study conducted in São Paulo in 2019 showed that the average birth weight was 1182 grams, a result like those presented in this study. 8,10 The weight of the NB interferes in the exteriorized portion of the blunt catheter, which will be smaller in NB with larger size while in premature NB the exteriorized portion will be larger. Randomization allowed a homogeneous sample, to eliminate a possible bias arising from the exteriorized portion of the catheter in each group studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In a study on the birth weight of NBs performed in Minas Gerais, 49% of these had a weight below 2500 grams, another study conducted in São Paulo in 2019 showed that the average birth weight was 1182 grams, a result like those presented in this study. 8,10 The weight of the NB interferes in the exteriorized portion of the blunt catheter, which will be smaller in NB with larger size while in premature NB the exteriorized portion will be larger. Randomization allowed a homogeneous sample, to eliminate a possible bias arising from the exteriorized portion of the catheter in each group studied.…”
Section: Discussionmentioning
confidence: 99%
“…Randomized cotrolled trial on cutting the peripherally inserted central catheter in neonates Wosnes T dos R, Giacomozzi CM, Giacomozzi LM, Silva RPVC showed 73.8% of catheters in central position, both studies with results like the present study, which obtained more than 80% of its catheters in central position. 6,8 During the use of the PICC, the reason for removal is a relevant predictor of care failures related to care with the catheter. Nursing professionals are primarily responsible for maintaining safety, since they provide direct patient care; however, there are many errors and adverse events, making patient safety a health challenge.…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico más identificado de los RN ingresados en la UCIN estudiada fue la prematuridad en ambos grupos, una realidad similar a la de la literatura nacional. Los estudios realizados en las UCIN brasileñas muestran una media del 80% de la población con diagnóstico de prematuridad, y el rango de edad gestacional más comúnmente observado es el de 29 a 36 semanas, que corresponde al 60% de la muestra [6][7][8][9] . En esta muestra, los RN con una edad gestacional superior a las 38 semanas fueron ingresados por dificultades respiratorias, hipoglucemia o asfixia perinatal.…”
Section: Discussionunclassified
“…5 En un estudio sobre el peso al nacer de los RN realizado en Minas Gerais, el 49% de estos presentaron peso inferior a 2500 gramos, otro estudio realizado en São Paulo, en 2019, mostró que el peso medio al nacer fue de 1182 gramos, resultado similar a los presentados en este estudio. 8,10 El peso del RN interfiere en la porción exteriorizada del catéter sin cortar, que será menor en los RN con mayor tamaño mientras que en los prematuros la porción Ensayo controlado aleatorio sobre el corte del catéter central de inserción periférica en neonatos.…”
Section: Discussionunclassified
See 1 more Smart Citation